The “Third World” in the 1990s: Problems and challenges - Heiko Körner (Intereconomics, 1994)
Given that the developing countries today present a highly differentiated picture, is it appropriate to continue to speak of a “Third World”? If so, how does this group of countries appear to the present-day observer? What is their position within the world economy? What problems and challenges are they facing?
Keywords: 330; Development Strategy